Maternal Health Literacy and Postpartum Depression: Recognition, Treatment Awareness and Help-Seeking Outcomes - Thomas, Treesa Sindhu P.; Leon, Leena; S, Neshwa Najuma T.; Francis, Rose Mary (Asian Journal of Biological and Life Sciences, 2026)
Background: Maternal health literacy plays a crucial role in postpartum mental health, influencing the recognition, understanding, and management of Postpartum Depression (PPD). Objectives: To examine the impact of maternal health literacy on symptom recognition, treatment awareness, help-seeking behavior, and recovery outcomes among postpartum mothers. Materials and Methods: A quantitative survey was conducted among 100 postpartum mothers in Ernakulam, Kerala, between six to twelve months after childbirth. Data were collected on awareness of PPD, sources of information, treatment knowledge, help-seeking behavior, and perceived barriers. Results: Although 96% of respondents were aware of PPD, only 34% knew where to seek professional help. Digital platforms (31%) and social media (21%) were the primary sources of information, whereas healthcare providers were underutilized (15%). A statistically significant association (p=0.002) was observed between understanding treatment options and willingness to seek help. Major barriers included stigma (47%), lack of knowledge (44%), and uncertainty regarding healthcare access (21%). Conclusion: The findings highlight the need to integrate maternal mental health education into prenatal and postnatal care, enhance awareness, and strengthen early intervention strategies. Improving health literacy may reduce stigma, encourage timely help-seeking, and improve maternal well-being, thereby mitigating long-term complications associated with PPD.
Keywords: Help-Seeking Behavior; Maternal Health Literacy; Mental Health Stigma; Postpartum; Depression